Crack Growth from Naturally Occurring Material Discontinuities in Operational Aircraft. (2015) - Jones, Rhys; Peng, Daren; Huang, Pu; Singh, Raman R.K.
Abstract: This paper focuses on problems associated with aircraft sustainment related issues and illustrates how cracks that grow from small naturally occurring material discontinuities in operational aircraft behave. The example discussed in this paper, which is associated with crack growth under a representative maritime aircraft load spectrum, when taken in conjunction with previous studies into cracks growing under combat aircraft load spectra illustrates how for cracks that grow from naturally occurring material discontinuities under such operational load spectra there is generally little crack closure so that the crack growth history from its initial equivalent pre-crack size (EPS) through to final failure can be easily and accurately computed.